2004
DOI: 10.1046/j.0022-202x.2004.22243.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interaction Between NRAS and BRAF Mutations and PTEN/MMAC1 Inactivation in Melanoma

Abstract: Extant evidence implicates growth factor signaling in the pathogenesis of many tumor types, including cutaneous melanoma. Recently, reciprocal activating mutations of NRAS and BRAF were found in benign melanocytic nevi and cutaneous melanomas. We had previously reported a similar epistatic relationship between activating NRAS mutations and inactivating PTEN/MMAC1 alterations. We thus hypothesized that BRAF and PTEN/MMAC1 mutations may cooperate to promote melanoma tumorigenesis. Overall, 40 of 47 (85%) melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
334
3
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(360 citation statements)
references
References 18 publications
15
334
3
8
Order By: Relevance
“…In addition, we also confirmed that BRAF and NRAS mutations are mutually exclusive (Maldonado et al, 2003). However, our data also suggest that as there is no selection for coupled PTEN and NRAS mutations, both PTEN and BRAF mutation commonly occur in the same cells, emphasizing that BRAF is downstream of NRAS and does not affect the PI3K/PTEN pathway (Tsao et al, 2004). By searching for similar patterns of copy number changes, 11 concomitantly altered genomic pairs appeared ( Table 2).…”
Section: G Jönsson Et Alsupporting
confidence: 72%
“…In addition, we also confirmed that BRAF and NRAS mutations are mutually exclusive (Maldonado et al, 2003). However, our data also suggest that as there is no selection for coupled PTEN and NRAS mutations, both PTEN and BRAF mutation commonly occur in the same cells, emphasizing that BRAF is downstream of NRAS and does not affect the PI3K/PTEN pathway (Tsao et al, 2004). By searching for similar patterns of copy number changes, 11 concomitantly altered genomic pairs appeared ( Table 2).…”
Section: G Jönsson Et Alsupporting
confidence: 72%
“…3 Although linked to exposure to ultraviolet light, it is widely accepted that both genotypic and phenotypic changes in melanocytes predispose to melanocyte transformation and the onset of melanoma. 4,5 Surprisingly, p53 mutations are very rare in melanoma, but activity is, however, impaired through direct or indirect inactivation of key elements of this pathway, including through the suppression of APAF-1 expression, 6 loss of PTEN function, 7 dysregulation of Bcl-2 expression, 8 upregulation of the anti-apoptotic protein Mcl-1 together with its altered slice variant expression 9,10 and the ER chaperone GRP78. [11][12][13] Oncogenic mutations, however, in the Ras/Raf pathway are the most well-described genetic mutations associated with melanoma development and progression.…”
mentioning
confidence: 99%
“…26,30,32,34,[36][37][38][66][67][68][69][70][71] Only one atypical Spitz nevus from the arm of a 22-year-old female had an NRAS mutation in our study. As expected, this lesion lacked a BRAF mutation, since NRAS and BRAF mutations are mutually exclusive events.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies have reported BRAF mutations in benign and malignant melanocytic lesions. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] However, a number of studies have failed to demonstrate BRAF mutations in Spitz nevi. 25,[40][41][42][43][44][45][46][57][58][59][60][61] Most of these studies analyzed only classic Spitz nevi.…”
mentioning
confidence: 99%